INDONESIAN TERM OF ADDRESS USTAD IN FILM UTTERANCES: FORMS, FUNCTIONS, AND SOCIAL VALUES - Nugraha, Sandy; Triwinarti, Wiwin (UI Scholars Hub, 2019)
This study analyzes the term of address ustad in Indonesian culture. Indonesia’s religious-themed movies may represent the use of the term of address ustad in daily conversation. In particular, this study aims to describe the patterns of form, the patterns of use, and the social values of the term of address ustad in film utterances. The data of the term of address ustad and its contexts are collected from the utterances in Indonesia’s four Islamic-themed movies. This descriptive qualitative study uses sociopragmatics approach in identifying the functions of the term of address in film discourse. The context of the utterances that contain the term of address ustad is identified using Hymes’ (1972) S.P.E.A.K.I.N.G model. This study concludes that: (1) form patterns of the term of address ustad include incomplete form ‘Stad’; title ‘Ustad’; kinship term + title, e.g. ‘Pak Ustad’, and title + personal name, e.g. ‘Ustad Syamsul’; (2) the term of address ustad has two functions: showing respect and showing closeness; (3) there are six characteristics of people who are commonly addressed as ustad in Indonesia, including Quran private teachers, prayer leaders, teachers in pesantrens (Islamic boarding schools), Islamic preachers in mosques, Islamic preachers in television shows, and pesantren leaders in villages; (4) the terms of address ustad is a title held at any time regardless of the situation. An ustad is still addressed as ustad even though he is not preaching at that moment.